Kdo prebiva na knjižnih policah v naši šolski knjižnici? - Škrlj, Gregor (Šolska knjižnica, 2016)
The paper presents lessons in the third grade, during which we assess the knowledge and skills gained by pupils in the first triennium while exploring the library. It presents the worksheet and individual tasks used for knowledge assessment, and the successful cooperation with third grade teachers.
Keywords: bibliopedagoško delo; iskanje; knjižnična vzgoja; knjižnično gradivo; postavitev; šolske knjižnice